Recent advances in melittin-based nanoparticles for antitumor treatment: from mechanisms to targeted delivery strategies - Yu, Xiang; Jia, Siyu; Yu, Shi; Chen, Yaohui; Zhang, Chengwei; Chen, Haidan; Dai, Yanfeng (Journal of nanobiotechnology, 2023)
As a naturally occurring cytolytic peptide, melittin (MLT) not only exhibits a potent direct tumor cell-killing effect but also possesses various immunomodulatory functions. MLT shows minimal chances for developing resistance and has been recognized as a promising broad-spectrum antitumor drug because of this unique dual mechanism of action. However, MLT still displays obvious toxic side effects during treatment, such as nonspecific cytolytic activity, hemolytic toxicity, coagulation disorders, and allergic reactions, seriously hampering its broad clinical applications. With thorough research on antitumor mechanisms and the rapid development of nanotechnology, significant effort has been devoted to shielding against toxicity and achieving tumor-directed drug delivery to improve the therapeutic efficacy of MLT. Herein, we mainly summarize the potential antitumor mechanisms of MLT and recent progress in the targeted delivery strategies for tumor therapy, such as passive targeting, active targeting and stimulus-responsive targeting. Additionally, we also highlight the prospects and challenges of realizing the full potential of MLT in the field of tumor therapy. By exploring the antitumor molecular mechanisms and delivery strategies of MLT, this comprehensive review may inspire new ideas for tumor multimechanism synergistic therapy.